2020
DOI: 10.1016/j.anai.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, severe asthma, and biologics

Abstract: A case of food-dependent exerciseinduced anaphylaxis by shrimp: fructose 1,6-bisphosphate aldolase is supposed as causative component despite negative allergen-specific IgE test (ImmunoCAP). Arerugi. 2019;68(1):48e53. 10. Kimura H, Inami M, Hamaguchi Y, et al. Food-dependent exercise-induced anaphylaxis due to shrimp associated with 43 kDa, a new antigen. J Dermatol. 2018;45(3):366e367.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…Few reports linked asthma to COVID-19 severity; however, in most of the studies, asthma was not identified as a risk factor for severe illness ( Morais-Almeida et al, 2019 ). Moreover, cases of COVID-19 patients with severe asthma were reported to have a good outcome despite expectations of severe infection and poor prognosis in this subset of patients ( Garcia-Moguel et al, 2020 ).…”
Section: The Association Between Covid-19 and The Most Common Chronicmentioning
confidence: 99%
“…Few reports linked asthma to COVID-19 severity; however, in most of the studies, asthma was not identified as a risk factor for severe illness ( Morais-Almeida et al, 2019 ). Moreover, cases of COVID-19 patients with severe asthma were reported to have a good outcome despite expectations of severe infection and poor prognosis in this subset of patients ( Garcia-Moguel et al, 2020 ).…”
Section: The Association Between Covid-19 and The Most Common Chronicmentioning
confidence: 99%
“…Recently obtained data has shown that in patients with COVID-19, eosinopenia developed during the infection. This data suggests that an elevation of the number of eosinophils could indicate an improvement of this disease [7].…”
Section: Introductionmentioning
confidence: 60%
“…Supporting this claim, Lommatzsch demonstrated that omalizumab could safely be continued during active COVID‐19 infection in a patient with allergic asthma 1 . There are other reports that treatment with benralizumab 2 and dupilumab 3 are not associated with significant negative impact. We had similar experience in a young patient with severe asthma who had previously been treated with dupilumab.…”
Section: Figurementioning
confidence: 90%